Two millennia of tropical cyclone-induced mud layers in a northern Yucatán stalagmite : multiple overlapping climatic hazards during the Maya Terminal Classic “megadroughts” - Frappier, Amy Benoit (2014)
An annually laminated stalagmite from the northern Yucatán Peninsula contains mud layers from 256 cave flooding events over 2240 years. This new conservative proxy for paleotempestology recorded cave flooding events with a recurrence interval of 8.3 years during the twentieth century, with the greatest frequency during the twentieth century and the least frequent during the seventeenth century. Tropical cyclone (TC) events are unlikely to flood the cave during drought when the water table is depressed. Applying TC masking to the Chaac paleorainfall reconstruction suggests that the severity of the Maya “megadroughts” was underestimated. Without a high-resolution radiometric geochronology of individual local TC events, speleothem isotope records cannot resolve whether the Terminal Classic Period in the northern Maya Lowlands was punctuated by several brief drought breaks with normal TCs, or whether the region was very dry and peppered by unusually severe and frequent hurricane seasons.